GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 472922671 species occurrences available in GBIF matching the query: HasCoordinate: true HasGeospatialIssue: false BasisOfRecord: Human Observation. The dataset includes 472922671 records from 9032 constituent datasets: Please see http://www.gbif.org/occurrence/download/0041018-160910150852091 for full list of all constituents.
Keywords: GBIF; biodiversity; species occurrences